FORMULATION OF OINTMENT FROM METHANOL EXTRACTS OFSENGGANI LEAVES (Melastoma malabathricum L.) WITH VARIATION OF OINTMENT BASE: FORMULASI SALEP DARI EKSTRAK METANOL DAUN SENGGANI(Melastoma malabathricum L.) DENGAN VARIASI BAHAN BERBASIS SALEP - Rina Kurniaty; Salimatun Nahar; Ika Rezvani Aprita (ROCE : Jurnal Pertanian Terapan, 2025)
Senggani (Melastoma malabatrichum L.) is a traditional medicinal plant. The chemical content, including saponins, tannins, flavonoids, quinones, and steroids, in senggani leaves provides antibacterial effects. Ointment preparations are semi-solid preparations that are used for the outside of the body by applying to the outside of the body in the affected area. This study is experimental, aiming to determine the physical characteristics of ointments from the methanol extract of senggani leaves using a variety of ointment bases, namely hydrocarbon ointment base (F1), absoprsi (F2), water-washed (F3), and water-soluble (F4). Evaluation of ointment preparations in each formula includesOrganoleptics, Homogeneity, pH, and Scatter. The results of the study of ointment preparations fromformulas in the form of semi-solid odor typical of seggani and blackish green (F1, F2, F4) and lightgreen (F3). Ointment preparations show homogeneous properties, with pH levels of 4.8 (F4), 5.0 (F3),and 6.1 (F2 and F1). The results showed that ointment preparations of methanol extract of sengganileaves that met the test requirements were only F2 and F3.